Loss-tolerant state engineering for quantum-enhanced metrology via the reverse Hong–Ou–Mandel effect - Alexander E. Ulanov (Nature Portfolio, 2016)
N00N states are promising for quantum communications and metrology, but are vulnerable to losses. Here the authors develop a technique for preparing high-fidelity two-photon N00N states in a loss-free fashion, and demonstrate enhanced phase sensitivity without requiring recombination.